Recycling of Disposable Face Mask: Experimental Studies on Different Types of Polymer Mixture - Widiastuti, Indah; Wijayanto, Danar Susilo; Nabila, Urfan (Graduate School of Universitas Syiah Kuala, 2024)
The COVID-19 pandemic has caused significant impacts on the environment since the use of disposable face masks leads to the accumulation of plastic waste. In this study, a two-step extrusion and injection molding was performed to manufacture polymer blends consisting of 80% used face mask and 20% fraction of one of these recycled polymer mixtures: polypropylene (PP), high-density polyethylene (HDPE), and PET. ASTM D256 standard was used to evaluate the mechanical properties of the resulting polymer blend materials, while the physical performance was assessed by analyzing the shrinkage. It was found that adding other polymeric mixtures could not enhance the mechanical properties of pure disposable face masks, as measured by the impact strength. However, incorporating the recycled polymer into the face mask mixture is revealed to decrease shrinkage. Observation of the morphology surface of the fracture impact specimen using a Scanning Electron Microscope (SEM) confirmed the less miscibility within the recycled polymer/face mask. The blend, which contains recycled PET, showed the lowest percentage of shrinkage. Taking advantage of its recyclability characteristic, this current work may provide an alternative approach for using the disposable face mask in low load-bearing applications.